Beyond Traditional Banking: Smart CRM Strategies for Next-Generation Financial Technology Peer To Peer Lending Trust - Muamar Ridho Ridho; Susy Hastanarini Hasta; Arnoldyth Rodes Medo Arnold (Institut Komunikasi dan Bisnis LSPR, 2025)
The financial technology (fintech) industry faces a consumer trust crisis due to the proliferation of illegal online lending practices that have damaged the reputation of the entire Peer-to-Peer (P2P) Lending ecosystem. This research aims to formulate a strategic Customer Relationship Management (CRM) model for rebuilding consumer trust in legitimate P2P Lending platforms. Using a systematic literature review (SLR) method following PRISMA 2020 guidelines, this study analyzes 10 academic studies published between 2003-2022. Literature searches were conducted through Scopus, Web of Science, and Google Scholar databases, focusing on CRM implementation in the fintech context and its relationship with consumer trust building. The research identifies five main CRM contribution themes: service personalization, transparency and effective communication, data security, education and financial literacy, and responsive and sustainable customer relationship management. Findings indicate that effective CRM implementation not only enhances customer satisfaction and loyalty but also serves as a key strategy in reputational risk mitigation and public trust recovery. This study recommends integrating advanced technology with humanistic approaches in CRM, as well as the importance of proactive education and consumer engagement to build a sustainable trust ecosystem in the fintech industry.